Non-music specialists 's perceptions on their effectiveness in teaching music in primary schools / Noraliah Sabrina Ahmad Jefry and Muhammad Syahidzan Othman - Ahmad Jefry, Noraliah Sabrina; Othman, Muhammad Syahidzan (2022)
The purpose of this study is to explore the non-music specialists' perceptions of their effectiveness in teaching music in primary schools. The focus of this thesis is to explore the perceptions of non-music specialists on the effectiveness of teaching and learning and also the difficulties faced bynon-music specialists in primary school and how they overcome the obstacles by increasing efficiencies that could support music teachers in the music classroom. The experiences of non-music specialists teaching in primary schools at Hulu Selangor, Selangor, were collected using a qualitative phenomenology study approach. Six non-music specialists in primary school were interviewed in semi-structured interviews. Three main themes evolved from the experiences of these non-music specialists. Teachers' perspectives on effective teaching and learning to teach music proved to be varied. The study suggests that non-music specialists depend more on feedback, which could develop their effectiveness in teaching and learning. The study makes a significant contribution to how non-music specialists' perceptions of teaching effectiveness benefit them in overcoming the challenges to teaching music education, such as a lack of musical ability, facility, and space, as well as their physiological state. These findings indicate that additional support for non-music specialists should indeed be made accessible, which could include support from the school, the Malaysian Ministry of Education (MOE), and policymakers.